Mental Health of Dentists during the COVID-19 Pandemic: A Critical Literature Review - Laureano, Isla Camilla Carvalho (2020)
The effects of the Coronavirus Disease 2019 (COVID-19) pandemic on the mental health of healthcare professionals has become a concern, particularly among those who are in close contact with infected patients, including dentists. The aim of this critical literature review was to analyze the possible implications of the COVID-19 pandemic on the mental health of dentists. This bibliographic search was carried out in the PubMed, Web of Science and Scopus databases, using the following search keywords “Psychiatry OR anxiety OR fear OR depression OR psychological distress OR mental health” AND “COVID-19 OR SARS-CoV-2” AND “Dentists OR dental practice. Original research publications that included data on the mental health status of dentists during the COVID-19 pandemic were included. Data were tabulated in Microsoft Excel 2016 for Windows and descriptively presented. Eleven publications were eligible for this review. All studies had cross-sectional design. Most of them used questionnaires created by study researchers (81.8%) and were carried out in Italy (45.5%). The number of participants ranged from 14 to 1,500. Effects on the mental health of dentists during the COVID-19 pandemic were observed, regarding fear of contamination, anxiety, concerns, stress, depression, job insecurity, subjective overload, perceived risk and feelings and emotions. It was concluded that the COVID-19 pandemic had negative impact on the mental health of dentists, with high prevalence of fear, anxiety and concern, among other psychological symptoms.